The Role of Ultrasound in Evaluating the Effect of Urate-lowering Drugs in Gout Patients - El-Mallah, Reem; Ibrahim, Rehab A.; El Attar, Enas A. (Current Rheumatology Reviews, 2022)
Background: Gout is one of the most common inflammatory arthritis, where identification of MSU crystals in synovial fluid is a widely used diagnostic measure. Ultrasonography has a great sensitivity in detecting signs of MSU deposits, such as tophi and double contour (DC), as mentioned in the latest gout criteria, allowing early clinical diagnosis and therapy. Objective: The objective of this study was to evaluate the changes in ultrasound of gout patients’ knee and 1st metatarsophalangeal joint (MTP1) after initiation of urate-lowering therapy (ULT) drugs in the six-month period. Methods: Forty-three patients, fulfilling the ACR/EULAR 2015 criteria of gout with a score of >8, were enrolled; they were in between attacks and not on ULT for the last 6 months, or SUA concentration (SUA) of >6.0 mg/dL. Full examination, evaluation of joints pain by visual analog scale (VAS), ultrasonography (US) for tophus and DC at the knee, and MTP1 were performed at baseline and at 3 and 6 months (M3, M6) after starting ULT. Result: After 6 months of treatment, patients reached the target SUA level showed higher disappearance of DC sign (p<0.05) and a decrease in tophus size (p<0.05). The percentage of tophus size at 6th month was 26.4% and 3% for DC sign disappearance, which was more at MTP1. Conclusion: Ultrasound examination in screening for gout tophi or DC sign before starting ULT and during follow-up is important and complements clinical examination.
Keywords: uric acid